Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1128/aem.03033-16
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Dynamics, and Interactions within a Model Multispecies Exoelectrogenic-Biofilm Community

Abstract: Anode-associated multispecies exoelectrogenic biofilms are essential for the function of bioelectrochemical systems (BESs). The individual activities of anodeassociated organisms and physiological responses resulting from coculturing are often hard to assess due to the high microbial diversity in these systems. Therefore, we developed a model multispecies biofilm comprising three exoelectrogenic proteobacteria, Shewanella oneidensis, Geobacter sulfurreducens, and Geobacter metallireducens, with the aim to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 62 publications
4
36
0
2
Order By: Relevance
“…Flavin molecules have been found as endogenous electron shuttles that can interact with the electron acceptor to promote ideal organism growth. 34 In our experiments, the FMN concentration increased aer the growth of bacterial cells to the log phase, which indicated that FMN plays an important role in extracellular electron transfer in the strain DIF1 and strain DIF2. This may also be shown by the current increase aer adding RF and FMN (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Flavin molecules have been found as endogenous electron shuttles that can interact with the electron acceptor to promote ideal organism growth. 34 In our experiments, the FMN concentration increased aer the growth of bacterial cells to the log phase, which indicated that FMN plays an important role in extracellular electron transfer in the strain DIF1 and strain DIF2. This may also be shown by the current increase aer adding RF and FMN (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Shewanella species were also shown to secrete avins as electron mediators, but direct contactdependent electron transfer was still the main pattern of electron transfer. 14,24,25,32,34 In our experiment, when the anode with the biolm was placed into a fresh anolyte, the redox activity was fairly weak. When a new anode was immersed in the spent anolyte, the redox peaks were obvious, as shown in Fig.…”
Section: Discussionmentioning
confidence: 66%
“…A biological approach comprises the genetic modification of electrochemically active microorganisms. The use of defined mixed cultures represents another option, because the electron transfer efficiency can be improved by mutual interactions between organisms , . In physico‐chemical approaches, the electrode surface and its interaction with the microorganisms as well as the application of redox mediators constitute a central aspect of this research .…”
Section: Microbial Fuel Cells: Setup and Extracellular Electron Transfermentioning
confidence: 99%
“…They range from improved anaerobic conditions for electrogens due to oxygen depletion to their extended substrate accessibility or their simultaneous utilization of different EET types , . Additionally, the current density could be increased to a total of 6000–6400 mA m −2 by cocultivating G. sulfurreducens (generating a current density in the corresponding pure culture of 4700 mA m −2 ), Geobacter metallireducens (600 mA m −2 ) and S. oneidensis (1300 mA m −2 ), which has been associated with both the upregulation of the central metabolism and cytochrome‐related gene expression as well as the interorganismal use of secreted redox mediators . Further investigations confirmed the positive effect of defined mixed cultures of G. sulfurreducens and S. oneidensis on one another based on the 38 % higher current density (5400 ± 700 mA m −2 ) and 35 % thicker biofilm dominated by G. sulfurreducens (93 ± 8 µm) in comparison to the individual pure cultures ( G. sulfurreducens with 3900 ± 900 mA m −2 and S. oneidensis with 340 ± 11 mA m −2 ) .…”
Section: Organism‐based Strategies To Improve the Extracellular Electmentioning
confidence: 99%
“…Most representatives of sulfidogenic bacteria have a nonspecific metal reductase enzyme system that allows them to use compounds of Fe(III), Mn(IV), U(VI), Cr(VI), Cu(II) and other metals as electron acceptors of anaerobic respiration (Kozlova et al, 2008). Soluble and insoluble metal compounds are reduced outside the cells by a system of membrane-bound metal reductases (multi-heme c-type cytochromes) (Gescher & Kappler, 2012;Richter et al, 2012;Breuer et al, 2015), therefore electrons are released into the medium, allowing these exoelectrogenic anaerobic bacteria to be used in the microbial fuel cells (MFC) as the high effective anode biocatalysts (Fitzgerald et al, 2013;Prokhorova et al, 2017;Simonte et al, 2017). Electric current generation by Desulfuromonas acetoxidans IMV B-7384 in a MFC was described (Bilyy et al, 2014;Vasyliv et al, 2015), and the interrelation between Fe(III) reduction and exoelectrogenesis performed by this bacteria in the MFC was established (Vasyliv et al, 2016).…”
Section: Introductionmentioning
confidence: 99%